Knowledge and practices of laboratory safety precautions and infection control procedures of dental technicians in Recto, Manila - So, Maria Michelle V.; Galban, Angelita (Adviser).
Dental technicians are exposed to physical, microbiological, and chemical hazards in their type of work. Laboratory safety precautions and infection control procedures have been made to protect the laboratory workers from these hazards. It is the objective of this study to describe the knowledge of the dental technicians employed in dental laboratories in Recto, Manila of the general laboratory safety precautions and infection control procedures, and their work practices regarding this aspect. Fifty-seven dental laboratory technicians employed in dental laboratories in Recto, Manila were included in the study. A three-page questionnaire in Pilipino was used to conduct the study. The answers were then tallied and tabulated, and percentages and averages were then computed. The study has shown that the dental technicians are knowledgeable of some of the safety and infection control precautions, however, practice of these precautions is generally lower than the practice. The more known precautions such as use of eyewear was observed by (56) 98% of the respondents, use of disinfectant soap by (53) 93%, handwashing by (52) 91%, use of face masks by (51) 89%, use of safety gloves by (44) 77%, labeling of chemical containers by (40) 70%, vaccination against Hepatitis B by (39) 68% and use of lab coats or gowns by (29) 51%. Reasons for non-practice included unavailability of materials (54%) and no sufficient knowledge (46%). It can be concluded that the knowledge of the dental technicians of the general laboratory safety precautions and infection control procedures is minimal. The unavailability of materials and lack of knowledge of the dental technicians are the reasons why the practice of these precautions is lower than the knowledge that these are to be
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.